Weight Loss and Eating Behavior following Vertical Banded Gastroplasty - van Hout, Gerbrand C. M. (Springer-Verlag, 2007)
BACKGROUND: Bariatric surgery is the treatment of choice for patients with morbid obesity. In addition to surgery, postoperative dietary behavior is an important mediator of weight loss and, therefore, critical in influencing outcome. Surgical treatment of obesity is not an alternative to dieting but a method to enforce dieting. METHODS: We evaluated early weight loss and postoperative eating behavior over time. Preoperatively as well as 6 months, 1 and 2 years after vertical banded gastroplasty (VBG), 91 patients were psychologically assessed using a semi-structured interview and a psychological questionnaire focusing on eating behavior. RESULTS: Over time, we found significant changes in weight, mostly in the 1st postoperative year (EWL= 52.0%); at 2 years, EWL was 61.5%. Patients reported substantial changes in feelings of hunger, appetite, satiety, and eating behavior; however, most improvements waned over time. In addition, there was a wide variability in changes within our patient group, and changes in weight loss appeared to be related to changes in restrained eating. CONCLUSION: VBG not only leads to considerable weight loss, but also to significant improvements in eating behavior, at least within 2 years. However, most improvements wane over time and not all patients profit in the same way.